Nation-building : beyond Afghanistan and Iraq - Fukuyama, Francis (Forum on constructive capitalism., 2006)
Bestselling author Francis Fukuyama brings together esteemed academics, political analysts, and practitioners to reflect on the U.S. experience with nation-building, from its historical underpinnings to its modern-day consequences. The United States has sought on repeated occasions to reconstruct states damaged by conflict, from Reconstruction in the South after the Civil War to Japan and Germany after World War II, to the ongoing rebuilding of Iraq. Despite this rich experience, there has been remarkably little systematic effort to learn lessons on how outside powers can assist in the building of strong and self-sufficient states in post-conflict situations. The contributors dissect mistakes, false starts, and lessons learned from the cases of Afghanistan and Iraq within the broader context of reconstruction efforts in other parts of the world, including Latin America, Japan, and the Balkans. Examining the contrasting models in Afghanistan and Iraq, they highlight the Coalition Provisional Authority in Iraq as a cautionary example of inadequate planning. The need for post-conflict reconstruction will not cease with the end of the Afghanistan and Iraq missions. This timely volume offers the critical reflection and evaluation necessary to avoid repeating costly mistakes in the future. Contributors: Larry Diamond, Hoover Institution and Stanford University; James Dobbins, RAND; David Ekbladh, American University; Michèle A. Flournoy, Center for Strategic and International Studies; Francis Fukuyama, Paul H. Nitze School of Advanced International Studies, Johns Hopkins University; Larry P. Goodson, U.S. Army War College; Johanna Mendelson Forman, UN Foundation; Minxin Pei, Samia Amin, and Seth Garz, Carnegie Endowment for International Peace; S. Frederick Starr, Central Asia-Caucacus Institute at Johns Hopkins School of Advanced International Studies; F.X. Sutton, Ford Foundation Emeritus; Marvin G. Weinbaum, University of Illinois at Urbana-Champaign.